Novel Association of WNK4 Gene, Ala589Ser Polymorphism in Essential Hypertension, and Type 2 Diabetes Mellitus in Malaysia. (29th May 2016) - Ghodsian, Nooshin; Ismail, Patimah; Ahmadloo, Salma; Heidari, Farzad; Haghvirdizadeh, Polin; Ataollahi Eshkoor, Sima; Etemad, Ali
Abstract : With-no-lysine (K) Kinase-4 (WNK4) consisted of unique serine and threonine protein kinases, genetically associated with an autosomal dominant form of hypertension. Argumentative consequences have lately arisen on the association of specific single nucleotide polymorphisms of WNK4 gene and essential hypertension (EHT). The aim of this study was to determine the association of Ala589Ser polymorphism of WNK4 gene with essential hypertensive patients in Malaysia. WNK4 gene polymorphism was specified utilizing mutagenically separated polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) method in 320 subjects including 163 cases and 157 controls. Close relation between Ala589Ser polymorphism and elevated systolic and diastolic blood pressure (SBP and DBP) was recognized. Sociodemographic factors including body mass index (BMI), age, the level of fasting blood sugar (FBS), low density lipoprotein (LDL), and triglyceride (TG) in the cases and healthy subjects exhibited strong differences (p < 0.05 ). The distribution of allele frequency and genotype of WNK4 gene Ala589Ser polymorphism showed significant differences (p < 0.05 ) between EHT subjects with or without type 2 diabetes mellitus (T2DM) and normotensive subjects, statistically. The WNK4 gene variation influences significantly blood pressure increase. Ala589Ser probably has effects on the enzymic activity leading to enhanced predisposition to the disorder.